IMPROVING THE QUALITY OF FOREIGN LANGUAGE TEACHING BY IMPLEMENTING NON-TRADITIONAL TEACHING METHODS IN HIGHER EDUCATION INSTITUTIONS (Scientific journal of the Fergana State University, 2023)
In this article, the need to use various tools to increase the effectiveness of the foreign language teaching process, including effective methods and methods that take into account the needs of language learners, is present in the foreign language curriculum and curricula. In order to identify the existing shortcomings and develop new useful types of them, there are opinions that educational programs and plans should be analyzed in detail. The purpose of the research is that foreign language teachers should have in-depth knowledge of primary education pedagogy and teaching methodology. According to the results of the research, it was concluded that foreign language teachers should improve their qualifications in colleges or universities.